Development of specific training load in boxing - Šiska, L.; Hubinak, A.; Krpska, P.; Brodani, J. (Journal of Physical Education and Sport, 2020)
Motor tests to verify the performance of athletes are an integral part of long-term sports training. The aim was to design a specific short-interval training load that could be used as a diagnostic testing tool, develop the relevant assessment methodology and identify its immediate effects on motor performance. The research set consisted of 45 subjects divided into three groups of 15 (women, men, boxers). The load exercise was designed as a physical equivalent of a boxing match with the duration of 3x3 min., and it consisted of repetitive power-speed sequences: a combination of two push-ups and one maximum-effort movement. The duration of one sequence was approximately 5 seconds. We counted the number of sequences during the 3x3 min. load. During the sequence, we measured the duration of the hand contact with the pad in the first and second push-up, and the time it took the subject to run around a dummy, the sum of which represents the sequence intensity. During the load, we also evaluated the drop in performance and gave the overall test score. In our best subject, the number of sequences decreased from 29 in the first round to 25 in the third round. The sequence intensity decreased from 3.52 ± 0.28s to 3.93 ± 0.28s p < 0.01. The total score decreased from 8.24 to 6.45 points. The performance drop varied from 9.5% to 20.5%. When evaluating the entire set, the boxers achieved the highest number of sequences p <0.01 and they also exhibited a decrease in performance between the rounds p <0.01. In view of sequence intensity, males and boxers achieved similar results p> 0.05, and no reduction of performance p> 0.05 was recorded between the rounds. The best total score was achieved by the boxers p <0.01; and they also showed a decrease in performance between the rounds p <0.01. The designed load exercise can serve as a useful training means for the development of special endurance, but also diagnostics.